Epigenetic and genetic mechanisms through which Myostatin regulates muscle wasting - Lua, Gavian Bing Jia (2016)
Myostatin (Mstn) is a secreted growth factor that negatively regulates proliferation and differentiation of myoblasts. While the downstream signaling pathways and targets genes of Myostatin have been well studied, the involvement of microRNAs (miRNAs) in Myostatin regulation of myogenesis remains to be fully characterized. Here in this thesis, we have performed miRNA microarray on RNA isolated from myoblast and myotube models of Myostatin gain- and loss-of-function. Subsequent bioinformatics analysis identified miR-34a as a downstream target of Myostatin. Molecular analysis confirmed that Myostatin transcriptionally upregulates miR-34a expression via NF-κB. Similar to the known effect of Myostatin, overexpression of miR-34a resulted in impaired myoblast proliferation and inhibited myogenic differentiation. Furthermore, AntagomiR-mediated knockdown of miR-34a not only enhanced myogenesis but also rescued Myostatin-mediated inhibition of myoblast proliferation and differentiation. Mechanistically, we find that miR-34a targets the MyoD transcription co-factor TCF12, thereby impairing MyoD function, reducing myogenin expression and preventing myogenic differentiation. Satellite cells are quiescent muscle stem cells that have critical functions in post natal muscle growth and repair. Quantitative PCR confirmed that miR-34a expression was elevated in quiescent satellite cells. However, upon activation of satellite cells in vitro the levels of miR-34a decreased. Similarly, in response to Notexin-induced injury and satellite cell activation, endogenous miR-34a levels were reduced until day 3 post-injury, which we propose is permissive for efficient satellite cell activation and muscle repair. Consistent with this, overexpression of miR-34a in Notexin-injured skeletal muscle led to reduced activation of satellite cells as indicated by low numbers of MyoD positive cells and eventual atrophy of regenerated skeletal muscle fibres. Further analysis confirmed that ectopic expression of miR-34a downregulates Notch1 and impedes Notch1 signaling, which we hypothesize is the molecular mechanism behind the impaired satellite cell activation. Given that Myostatin negatively regulates satellite cell activation we propose that Myostatin functions through miR-34a to regulate satellite cell activation and proliferation and resulting muscle healing. Collectively the results presented here identify a novel Myostatin target and outlines a new mechanism through which Myostatin regulates myogenesis.